Suboptimal anticoagulation with pre-hospital heparin in ST-elevation myocardial infarction - Hermanides, Renicus S.; Ottervanger, Jan Paul; Dambrink, Jan-Henk E.; Boer, Menko-Jan de; Hoorntje, Jan C. A.; Gosselink, A. T. Marcel; Suryapranata, Harry; Zijlstra, Felix; van ’t Hof, Arnoud W. J.; the Zwolle Myocardial Infarction Study Group; on behalf of (Thrombosis and Haemostasis, 2011)
This is a prospective, observational study performed in all consecutive ST-elevation myocardial infarction (STEMI) patients who had activated clotting time (ACT) measurement on arrival in the cathlab before coronary angiography. We studied the therapeutic effects of a pre-hospital fixed heparin bolus dose in consecutive patients with STEMI. A total of 1,533 patients received pre-hospital administration of aspirin, high dose clopidogrel (600 mg) and a fixed bolus dose of 5,000 IU unfractionated heparin (UFH), according to the national ambulance protocols. Some patients were also treated with glycoprotein IIb/IIIa inhibitors (GPI) in the ambulance. A therapeutic ACT range was defined according to the ESC guidelines as 200–250 seconds when patients had GPI pretreatment and 250–350 seconds when no GPI pretreatment. Of the 1,533 patients, 216 patients (14.1%) had an ACT within the therapeutic range, 82.3% of the patients had a too low ACT, whereas 3.5% of the patients had a too high ACT. After multivariable analysis, the only independent predictor of a too low ACT was increasing weight (odds ratio 1.02/kg, 95% confidence interval 1.01–1.03, p=0.001). Patients with a too low ACT had less often an open infarct related vessel (initial TIMI flow 2,3) as compared to patients with an ACT in range (36.5% vs. 45.9%, p=0.013). In only a minority of patients with STEMI, pre-hospital treatment with a fixed bolus dose UFH is within the therapeutic ACT range. Increased weight is an independent determinant of a too low ACT. We strongly recommend weight adjusted administration of UFH in the ambulance.
Keywords: Activated clotting time; fixed bolus dose; unfractionated heparin; ST-elevation myocardial infarction; primary percutaneous coronary intervention